Feeling scale, when can i use in elderly? A brief review - Raul Cosme Ramos Prado; Rodrigo Silveira; Ricardo Yukio Asano (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2021)
Introduction: the Feeling Scale (FS) is an inexpensive and affordable tool that measure the affective responses and is used to prescription and control physical exercise intensity. Overall, the FS is used in several age groups, such as children and elderly. The particularity of elderly generates the necessity to better clarify how we can use the FS. Objective: the present review sought to verify which moments we can evaluate the FS in elderly. Materials and Methods: a brief search strategy found seven studies to current review. Results: overall, the selected studies used the FS before, during and after the exercise session, showing the practical application of this tool to prescription and in control of elderly feeling. Conclusion: we concluded that the FS can used to control feeling and prescription of exercise of elderly at the moments before, during and after sessions.